Early Oligocene chinchilloid caviomorphs from Puerto Rico and the initial rodent colonization of the West Indies. Issue 1920 (12th February 2020) - Marivaux, Laurent; Vélez-Juarbe, Jorge; Merzeraud, Gilles; Pujos, François; Viñola López, Lázaro W.; Boivin, Myriam; Santos-Mercado, Hernán; Cruz, Eduardo J.; Grajales, Alexandra; Padilla, James; Vélez-Rosado, Kevin I.; Philippon, Mélody; et al.
Abstract : By their past and present diversity, rodents are among the richest components of Caribbean land mammals. Many of these became extinct recently. Causes of their extirpation, their phylogenetic affinities, the timing of their arrival in the West Indies and their biogeographic history are all ongoing debated issues. Here, we report the discovery of dental remains from Lower Oligocene deposits ( ca 29.5 Ma) of Puerto Rico. Their morphology attests to the presence of two distinct species of chinchilloid caviomorphs, closely related to dinomyids in a phylogenetic analysis, and thus of undisputable South American origin. These fossils represent the earliest Caribbean rodents known thus far. They could extend back to 30 Ma the lineages of some recently extinct Caribbean giant rodents ( Elasmodontomys and Amblyrhiza ), which are also retrieved here as chinchilloids. This new find has substantial biogeographic implications because it demonstrates an early dispersal of land mammals from South America to the West Indies, perhaps via the emergence of the Aves Ridge that occurred ca 35–33 Ma (GAARlandia hypothesis). Considering both this new palaeontological evidence and recent molecular divergence estimates, the natural colonization of the West Indies by rodents probably occurred through multiple and time-staggered dispersal events (chinchilloids, then echimyid octodontoids (spiny rats/hutias), caviids and lastly oryzomyin muroids (rice rats)).